Bouncing back from COVID-19: Lessons from the food crisis - Babu, Suresh Chandra; Dassani, Vaishali (M. S. Swaminathan Research Foundation, 2020)
Globally, COVID-19 is a public health emergency with grave impact on the population of the world, especially the poor and marginalized. It is estimated that 140 million additional people could fall into extreme poverty this year as a result of the virus, thus increasing food and nutrition insecurity.While much has been written about the potential impact, little is known on how to bounce back from such outbreaks.